Furgensi Infrastruktur Dalam Surat An-Nahl Ayat 15 Menurut Ibn Jarir Al-Tabari Dan hamka - Jaka Ghianovan (Jurnal Semiotika Quran, 2023)
The existence of a country is said to be advanced if it meets several conditions, one of which is a good and strong infrastructure. The urgency of this aims to sustain human life. Infrastructure consists of several types, namely: 1) Economic Infrastructure which revolves around services that produce production and final consumption as well as public facilities; 2) Social Infrastructure which is engaged in health, education and tourism; 3) Administrative Infrastructure / Institutions in the field of law enforcement, population administration and culture. Infrastructure is discussed in the Qur'an Surah An-Nahl verse 15 such as the creation of mountains, rivers and roads. Ibn Jarir Al-Tabari explains that the creation of rivers (Anharan) and roads (Subulan) aims to facilitate transportation connectivity between regions and to make it easier for humans to get the gifts of Allah SWT. Hamka also explained that the existence of several things mentioned in Surah AnNahl verse 15 such as rivers and roads is the lifeblood of mankind as has happened since the beginning of human civilization, so this is very urgent for the development of the country